Evaluation of Sustainability Determinants of Small Farming Systems via Participatory Modeling and Fuzzy Multi-Criteria Processes: The Case Study of Heliciculture in Greece - Hatziioannou, Marianthi; Kokkinos, Konstantinos (Frontiers in Sustainability, 2021)
Feasibility and sustainability of small-scale farming systems are the most critical factors that determine future investments of urban agro-farming while promoting eco-systematic livelihood development and biodiversity. The determination and the diversification of the ambivalent and heterogeneous factors that affect the investment decision making of small farming systems is studied in this work via the application of participatory modelling methodology of regional stakeholders. Defuzzification of the participants’ categorical feedback is succeeded applying Fuzzy Analytical Hierarchy Process (F-AHP) to set the pairwise weight matrix of the determinants suggested by the stakeholders. At a second phase, an innovative Fuzzy Cognitive Map (FCM) model is utilized to determine the weighted inter-causalities between all agricultural, environmental, and socio-economic criteria from the F-AHP output. Apart from the concept circumscription, we use the FCM to provide an in-depth scenario analysis including steady state and dynamic evaluation of driver concepts to receiver concepts in the model. The methodology is applied for the case study of heliciculture farming systems in Greece. Results show that sustainability is affected primarily by agricultural and inventory factors and secondarily by social and environmental factors identifying such cradle-to-farm gate life cycle assessment to be of low carbon footprint.